2009
DOI: 10.1542/peds.2008-1222
|View full text |Cite
|
Sign up to set email alerts
|

Differential Patterns of 27 Cord Blood Immune Biomarkers Across Gestational Age

Abstract: Biomarkers have different directions of association with prematurity; for significant biomarkers, the strength of association increases with biomarker concentration. Our results provide important information that could be used to guide additional studies aimed at determining mechanisms that contribute to preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 31 publications
5
106
1
2
Order By: Relevance
“…In this study, the higher levels of IL6 and IL8 in premature versus full-term infants are consistent with similar results in dried infant blood samples (38). Higher IL6, IL8, and MCP1 were found in cord blood from lower GA infants compared with full-term neonates (39). IL6 and IL8 were higher in the amniotic fluid of patients with premature labor or preterm premature rupture of membrane (40).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the higher levels of IL6 and IL8 in premature versus full-term infants are consistent with similar results in dried infant blood samples (38). Higher IL6, IL8, and MCP1 were found in cord blood from lower GA infants compared with full-term neonates (39). IL6 and IL8 were higher in the amniotic fluid of patients with premature labor or preterm premature rupture of membrane (40).…”
Section: Discussionsupporting
confidence: 85%
“…This finding was also described by Matoba et al who quantified twenty-seven types of cytokines in cord blood at different gestational ages and found that MCP-1 was the one that was most strongly associated with PTB [40]. Significantly higher levels of MCP-1 have also been measured in cervicovaginal fluid [41] …”
Section: Page 6 Ofsupporting
confidence: 77%
“…MIF has been found in cord blood (32,33). However, to the best of our knowledge, no data are available in blood of term and preterm neonates.…”
Section: Discussionmentioning
confidence: 94%